Should Contact Bans Be Lifted in Germany? A Quantitative Prediction of Its Effects - Jean Roch Donsimoni; René Glawion; Bodo Plachter; Constantin Weiser; Klaus Wälde (Center for Economic Studies and ifo Institute (CESifo), 2020)
Many countries consider the lifting of restrictions of social contacts (RSC). We quantify the effects of RSC for Germany. We initially employ a purely statistical approach to predicting prevalence of COVID19 if RSC were upheld after April 20. We employ these findings and feed them into our theoretical model. We find that the peak of the number of sick individuals would be reached already mid April. The number of sick individuals would fall below 1,000 at the beginning of July. When restrictions are lifted completely on April 20, the number of sick should rise quickly again from around April 27. A balance between economic and individual costs of RSC and public health objectives consists in lifting RSC for activities that have high economic benefits but low health costs. In the absence of large-scale representative testing of CoV-2 infections, these activities can most easily be identified if federal states of Germany adopted exit strategies that differ across states.
Keywords: I18; E17; C63; 330; COVID19; SARS-CoV-2; forecast; Germany; epidemic; pandemic